ANALISIS KEPUASAN KARYAWAN BEKERJA DI PTPN V KEBUN SEI KENCANA DESA SENAMA NENEK KECAMATAN TAPUNG HULU KABUPATEN KAMPAR - Febrinawati '; Eliza '; Eri Sayamar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study was 1) to determine the characteristics of employees of oil palm and rubber crops in PT. PTPN V Gardens Sei Kencana; 2) to analysis level of employee satisfaction palm oil and rubber plant in PT. PTPN V Gardens Sei Kencana. The research was conducted from March 2015. The method used is survey method. Sampling was done by purposive sampling with criteria for implementing employee who has a leadership position as the bottom and the bottom of the employees working in the field in rubber and palm oil as well as employees who work in the office PTPN V Gardens Sei Kencana. Research shows that employees who work in PTPN V Gardens Sei Kencana dominant male is 84.38% with an average age of 42 years where the high school level of education of employees is 75.00%, the average length of work employees are encouraged 17 years, and salary   s> 2,000,000 has the largest number that is 64.06%. Analysis of the level of satisfaction of employees working at getting that level of satisfaction with the supervisor has the highest score of 3.41 in the category "satisfied" followed by the level of satisfaction with the job got a score of 3.24 with the category "somewhat satisfied" then the level of satisfaction with co-workers obtained a score 3,17 with the category "somewhat satisfied" while the level of satisfaction with salaries get a score of 2.84 with the category "quite satisfied" and the lowest scores are at a level of satisfaction with the campaign that is 2.59 with the category of "less satisfied". So that the average level of satisfaction of employees working in PTPN V Gardens Sei Kencana is at 3.05 scores in the category "fairly satisfied".     Keywords: PTPN V Gardens Sei Kencana, Factor Satisfaction, Employee Satisfaction